1987
DOI: 10.1007/bf00041480
|View full text |Cite
|
Sign up to set email alerts
|

Increased frost tolerance and amino acid content in leaves, tubers and leaf callus of regenerated hydroxyproline resistant potato clones

Abstract: Sohumtuberosum, potato, amino acids, amino acid analogue resistance, frost tolerance, plant regeneration, proline, somaclonal variation. SUMMARY A number of previously selected hydroxyproline (hyp) resistant cell lines of a diploid potato (Solunum tuberosum L., clone H2578, 2n=2x=24) could be regenerated into plants which were further analysed. Hyp resistance, although lower than in the originally selected calli, was still present in regenerated shoots and in callus initiated from these shoots and it was not l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Proline levels can be manipulated in some species by in vitro selection in the presence of hydroxyproline (Van Swaaij et al 1986, 1987Dix 1993). Hydroxyproline is a toxic analogue of the amino acid proline and selection in the presence of hydroxyproline can lead to proline over-accumulation in cell lines and eventually to plants with heritable stress resistance (Riccardi et al 1983;Dorffling et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…Proline levels can be manipulated in some species by in vitro selection in the presence of hydroxyproline (Van Swaaij et al 1986, 1987Dix 1993). Hydroxyproline is a toxic analogue of the amino acid proline and selection in the presence of hydroxyproline can lead to proline over-accumulation in cell lines and eventually to plants with heritable stress resistance (Riccardi et al 1983;Dorffling et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…tuberosum tuber cannot survive a temperature of -3°C and lower. The foliage dies at temperatures of -4°C (van Swaaij et al, 1987;Vayda, 1994). Dale (1992) reports that potato tubers are destroyed by a frost period of 25 hours at -2°C or a frost period of five hours at -10°C.…”
Section: A Cultivationmentioning
confidence: 99%
“…Amino acid analogue-resistant mutants which overproduce the specific amino acid have been found in bacteria (Czonka, 1981 ;Sugiura & Kisumi, 1985) as well as plants (Widholm, 1976 ;Kueh & Bright, 1982 ;Van Swaaij et al ., 1986 ;Mori et al ., 1989) . It has been reported that free proline-accumulating cell lines resistant to a proline analogue show increased resistance to stresses such as salt (Riccardi et al ., 1983) and freezing (Van Swaaij et al ., 1986, 1987 . Van Swaaij et al .…”
Section: Introductionmentioning
confidence: 99%